PENGARUH PUPUK KOTORAN WALET DAN JARAK TANAM TERHADAP PERTUMBUHAN DAN HASIL BAWANG DAUN (Allium Fistulosum L.) - Sundari Sundari; Ahmad Sawalin (Agriculture Faculty, University of Kutai Kartanegara, Indonesia, 2019)
The aim of this research to discover the effect of swallow manure and spacing and interaction with growth and leek results (Allium fistulosum L.). The researcher conducts this research from May until July 2019 at Sumber Sari village, Loa Kulu sub-district, Kutai Kartanegara regency. This research was arranged in Randomized Block Design (RBD) with 4x3 factorial with three replications. The first was swallow manure (g) consisting of 4 levels, namely g0 (control or no treatment) g1 (0.5 kg plot-1) g2 (1.0 kg plot-1) and g3 (1.5 kg plot-1) and the second factor is the spacing (j) which consists of 3 level, namely j1 (15cm x 20 cm), j2 (20cm x 20cm), j3 (25cm x 20cm).The result showed that the effect of swallow manure had no significant by effect to the observation parameters. The highest average of yield of t ha-1 crops is g3 (1.5 kg plot-1) with an average yield of 5.40 t ha-1 and the lowest yield of crop yields t ha-1 is in g1 (0.5 kg plot-1) with an average yield 5.00 t ha-1. The result showed that plant spacing did not significantly affect the observation parameters. The treatment of j1 (15cm x 20cm) gives the highest towards the crop yield t ha-1 with an average yield of 6.03 t ha-1, besides that treatment of j3 (25cm x 20cm) gives the lowest yield towards the crop yield t ha-1 (ton) with an average of 3.71 t ha-1.The result of the interaction between the effect of swallow manure and plant spacing did not significant by affect to all the treatments. The highest average yield of t ha-1 crops was at g2j1 (1.0 kg plot-1 and 15cm x 20cm) with a yield of 6.40 t ha-1. The lowest average yield of t ha-1 plants was g1j3 (0.5 kg plot 1 and 25 cm x 20cm) with a yield of 3.32 t ha-1.